MMR Immunization and Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The risk of seizures following MMR or MR immunization is evaluated in a retrospective cohort study conducted among 18,364 Tennessee children from The Department of Preventive Medicine, Vanderbilt University School of Medicine, Nashville, TN.